In-situ irradiation-induced studies of grain growth kinetics of nanocrystalline UO2. (1st June 2022) - Yu, Zefeng; Xu, Xinyuan; Chen, Wei-Ying; Sharma, Yogesh; Wang, Xing; Chen, Aiping; Ulmer, Christopher J.; Motta, Arthur T.
Abstract: The thermal conductivity of UO2 fuel needs to be high enough to dissipate the heat generated from the fission reaction. Since grain size affects thermal conductivity and grain size can evolve with irradiation, it is critical to understand in-reactor UO2 grain growth. Most studies of grain growth in UO2 are based on thermally driven processes at elevated temperatures. However, studies have shown that grain growth can occur even at cryogenic temperatures by ballistic processes. Such irradiation-induced grain growth in UO2 is yet to be studied. Advanced in-situ Kr ion irradiation and transmission electron microscopy were systematically performed on nanocrystalline UO2 thin films at temperatures ranging from 50 K to 1073 K; grain growth was observed at all temperatures. A combination of manual and machine learning techniques was used to measure and plot grain size evolution against irradiation fluence at various irradiation temperatures. The machine learning method has significantly improved the analysis efficiency and reduced human labors. The grain diameter data were fitted using classical grain growth and thermal spike models to describe grain growth kinetics with and without irradiation effect. Grain growth during low temperature irradiation (≤ 475 K) can be well described by the thermal spike model. Above 475 K, there were additional thermally assisted processes that further accelerate the grain growth. At the highest irradiation temperature about 1075 K, both irradiation-induced dislocation loops and cavities/bubbles were observed to form in the UO2 . The effects of irradiation-induced defects on grain growth kinetics are discussed. Graphical abstract: Image, graphical abstract